2020
DOI: 10.47344/iysw.v9i0.199
|View full text |Cite
|
Sign up to set email alerts
|

Does Discussion Have Effect on Students’ Responses?

Abstract: Peer instruction teaching method has become an efficient learning strategy at all education grades. Peer teaching method developed by Eric Mazur can be defined as a technique in which participants actively participate in the education process by discussing in a peer group and helping each other in the group during the lesson. The aim of the present research was to investigate the effect of discussion in peer instruction techniques during the lecture. The application was carried out five weeks with 30 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This showed that discussion is an effective peer instruction tool and that discussion has a positive effect on correcting students' incorrect answers. The result is consistent with previous studies in this area (Brooks & Koretsky, 2011;Bruck & Towns, 2009;Crouch & Mazur, 2001;Giuliodori, Lujan & Di Carlo, 2006;Kaymak, 2020;Lasry et al 2009;Morgan & Wakefield. , 2012;Porter et al 2011b;Smith et al, 2009;Straw, Wicker & Harper, 2021;Willoughby, 2011).…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This showed that discussion is an effective peer instruction tool and that discussion has a positive effect on correcting students' incorrect answers. The result is consistent with previous studies in this area (Brooks & Koretsky, 2011;Bruck & Towns, 2009;Crouch & Mazur, 2001;Giuliodori, Lujan & Di Carlo, 2006;Kaymak, 2020;Lasry et al 2009;Morgan & Wakefield. , 2012;Porter et al 2011b;Smith et al, 2009;Straw, Wicker & Harper, 2021;Willoughby, 2011).…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…After the first 6-week phase, the opinions of the students about the discussion section were compiled and evaluated using a 5-point Likert-type scale. Kaymak (2020) investigated the effect of the discussion section on peer instruction during the lesson. The application was carried out with 30 students at Süleyman Demirel University for five weeks.…”
Section: Change Of Answersmentioning
confidence: 99%
See 1 more Smart Citation